Peningkatan Keterampilan Bertanya Lanjutan Mahasiswa Melalui Model Pembelajaran Direct Instruction - Ira Restu Kurnia (Universitas PGRI Semarang, 2022)
This research is motivated by the low ability of students advanced asking skill . The difficulty of students in compiling quality questions is a problem that must be corrected in a lesson. For this reason, researchers apply learning by using an appropriate model to improve students advanced asking skill, namely the Direct Instruction learning model. Direct Instruction was chosen as a model that can increase student activity in the learning process. The subjects of this study were students of 19B1 Elementary School Teacher Education Study Program, Pelita Bangsa University, Central Cikarang District, Bekasi Regency. The research method used is Classroom Action Research with a Kemmis and Tagart design (Wiriatmadja, 2005) by using question instruments and student activity sheets. Overall, the results of the study show that students advanced asking skill in learning always show an increase in each cycle. The increase in the percentage increase in achievement in this study covers aspects of students' knowledge and advanced questioning skills. In the aspect of knowledge, the percentage of the first cycle reached 78.25%, the second cycle reached 84.50%, the third cycle reached 90.63%. Meanwhile, in advanced questioning skills, the percentage of the first cycle reached an average of 22.40%, the second cycle reached 68.18%, and in the third cycle it reached 91.38%. So this research it can be concluded that the Direct Instruction learning model can improve students' advanced questioning skills.